Extracellular proteolytic enzymes produced by human pathogenic vibrio species - Miyoshi, Shin-Ichi (Frontiers in Microbiology, 2013)
Bacteria in the genus Vibrio produce extracellular proteolytic enzymes to obtain nutrients via digestion of various protein substrates. However, the enzymes secreted by human pathogenic species have been documented to modulate the bacterial virulence. Several species including Vibrio cholerae and V. vulnificus are known to produce thermolysin-like metalloproteases termed vibriolysin. The vibriolysin from V. vulnificus, a causative agent of serious systemic infection, is a major toxic factor eliciting the secondary skin damage characterized by formation of the hemorrhagic brae. The vibriolysin from intestinal pathogens may play indirect roles in pathogenicity because it can activate protein toxins and hemagglutinin by the limited proteolysis and can affect the bacterial attachment to or detachment from the intestinal surface by degradation of the mucus layer. Two species causing wound infections, V. alginolyticus and V. parahaemolyticus, produce another metalloproteases so-called collagenases. Although the detailed pathological roles have not been studied, the collagenase is potent to accelerate the bacterial dissemination through digestion of the protein components of the extracellular matrix. Some species produce cymotrypsin-like serine proteases, which may also affect the bacterial virulence potential. The intestinal pathogens produce sufficient amounts of the metalloprotease at the small intestinal temperature; however, the metalloprotease production by extra-intestinal pathogens is much higher around the body surface temperature. On the other hand, the serine protease is expressed only in the absence of the metalloprotease.